Kajian Analisis Risiko Keselamatan Kerja di Workshop Traktor - Pramuhadi, Gatot; Herodian, Sam; Anhar, Fahri (Jurnal Agricultural Biosystem Engineering, 2025)
Work safety has the main goal of protecting workers from risks associated with their work in the workshop area. The purpose of this study is to identify, analyze, and control risks, as well as the dangers of work safety in one of the large workshops of PT United Tractors Jakarta Branch in the period June 2023 to August 2023. The results show that based on the results of the identification of 233 potential risks, it has been determined that ergonomic hazards emerged as a top priority, especially the risk of injury to fingers and hands. Initial risk assessment shows that almost all dangers are classified as moderate and unacceptable risk. After the application of control obtained a relative risk value of 0.0386 and relative risk reduction of 96.14%. The risk control approach shows that there are 10 preventive actions, 7 corrective actions, 8 detective actions, and 7 directive actions. Recommendations for controlling ergonomic hazards are 3 preventive actions, 3 corrective actions, 3 detective actions, and 2 directive actions at the risk of finger injury. Keywords: The Danger of Ergonomics, Relative Risk, Relative Risk Reduction, Risk Control Techniques.